2011
DOI: 10.1038/nchembio.563
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the ligand-controlled organization of the SAM-I riboswitch

Abstract: S-adenosylmethionine (SAM) riboswitches are widespread in bacteria, and up to five different SAM riboswitch families have been reported, highlighting the relevance of SAM regulation. On the basis of crystallographic and biochemical data, it has been postulated, but never demonstrated, that ligand recognition by SAM riboswitches involves key conformational changes in the RNA architecture. We show here that the aptamer follows a two-step hierarchical folding selectively induced by metal ions and ligand binding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
172
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(196 citation statements)
references
References 51 publications
(74 reference statements)
21
172
3
Order By: Relevance
“…For example, Mg 2+ binding to the aptamer promotes the formation of the pseudoknot interaction, which was previously shown to be also stabilized in presence of SAM. 48 In addition, Mg 2+ binding induces the P2-P3 helical stacking as well as a close juxtaposition between helices P1 and P3, 23 the latter being consistent with SAXS experiments. 27,53 Disruption of the pseudoknot interaction was found to perturb P1-P3 close juxtaposition, which supports the idea that the pseudoknot may be used as a lever to correctly position P3 close to P1, via the P2-P3 helical stacking (Fig.…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 71%
See 4 more Smart Citations
“…For example, Mg 2+ binding to the aptamer promotes the formation of the pseudoknot interaction, which was previously shown to be also stabilized in presence of SAM. 48 In addition, Mg 2+ binding induces the P2-P3 helical stacking as well as a close juxtaposition between helices P1 and P3, 23 the latter being consistent with SAXS experiments. 27,53 Disruption of the pseudoknot interaction was found to perturb P1-P3 close juxtaposition, which supports the idea that the pseudoknot may be used as a lever to correctly position P3 close to P1, via the P2-P3 helical stacking (Fig.…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 71%
“…3A). 23 In agreement with this model, it was previously found that the folding of the kink-turn motif located in the P2 helical domain is crucial for the structure and ligand binding activity of the SAM-I aptamer. 46,50 Our study also revealed that SAM binding to the aptamer produces a second folding transition involving the stacking of stems P1 and P4.…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 58%
See 3 more Smart Citations